Association of apolipoproteins and lipoprotein(a) with metabolic syndrome: a systematic review and meta-analysis - Ulloque-Badaracco, Juan R. (2023)
Background & aims: Apolipoproteins and lipoprotein(a) are associated with various cardiometabolic diseases, including insulin resistance, diabetes mellitus, hypertension, dyslipidemia, among others. This systematic review and meta-analysis was conducted to evaluate the association of these markers with metabolic syndrome (MetS). Methods: We ran a systematic search through PubMed, Scopus, Embase, Ovid/Medline, and Web of Science on March 15, 2023. No language or date restrictions were applied. The only synthesised effect measure reported was the odds ratio (OR) with its corresponding 95% confidence interval (95% CI). We utilised the random-effects model for the quantitative synthesis. Results: We analysed 50 studies (n = 150 519) with different definitions for MetS. Increased ApoB values were associated with MetS (OR = 2.8; 95% CI: 2.44–3.22; p < 0.01, I2 = 99%). Decreased ApoA1 values were associated with MetS (OR = 0.42; 95% CI: 0.38–0.47; p < 0.01, I2 = 99%). Increased values of the ApoB/ApoA1 ratio were associated with MetS (OR = 4.97; 95% CI: 3.83–6.44; p < 0.01, I2 = 97%). Decreased values of Lp(a) were associated with MetS (OR = 0.89; 95% CI: 0.82–0.96; p < 0.01; I2 = 92%). Conclusions: Increased values of ApoB and ApoB/ApoA1 ratio are associated with MetS, while decreased values of ApoA1 and Lp(a) are associated with MetS. These findings suggest that these lipid markers may serve as potential indicators for identifying subjects at risk of developing MetS. However, further research is required to elucidate the underlying mechanisms of these associations.